Clay mineral screening method for preparing two-dimensional channel film
By classifying and screening clay minerals by layer charge density and film flatness, the method addresses the diversity challenge, enabling efficient selection of suitable raw materials for two-dimensional channel films, ensuring high-quality nanochannel membranes.
Patent Information
- Application Number
- CN202411233043.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-04
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-04
AI Technical Summary
The challenge lies in efficiently screening clay minerals for preparing two-dimensional channel films due to their family diversity and varying layer charge densities, which affect exfoliation and film orderliness, leading to difficulties in selecting suitable raw materials for high-quality nanochannel membranes.
A method is developed to classify clay minerals by layer charge density, followed by ultrasonic treatment to obtain nanosheets, and then screen them based on size and thickness criteria, culminating in a film flatness test to select suitable clay materials for two-dimensional channel films.
This method quickly and efficiently identifies clay minerals that are easy to peel and assemble into films, filling the gap in screening methods for two-dimensional channel films, ensuring high-quality nanochannel membrane production.
Smart Images

Figure CN119125200A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of testing, and in particular, to a method for screening clay minerals for preparing two-dimensional channel films. Background Art
[0002] Membrane separation is a selective separation by placing a barrier of isolating material between two phases or media, which allows one or more components to selectively enter another medium from one medium in the presence of an appropriate driving force. The core of membrane separation technology is the membrane material. Traditional membranes are mostly porous organic polymers, but the "trade-off" effect is still a huge challenge, that is, improving membrane selectivity will reduce its flux (Chem. Soc. Rev., 2020, 49, 1071-1089).
[0003] In recent years, two-dimensional nanochannel films with nano / sub-nano dimensions, prepared by layer-by-layer assembly of nanosheets with atomic-level thickness, can achieve highly selective separation of various ions with small size differences because their channels can be precisely controlled in the sub-nanometer range (Angew. Chem. Int. Ed. 2021, 60, 1-6). At the same time, the transmission rate of ions in the channel is thousands of times that in the macroscopic fluid, achieving high throughput and showing excellent ion screening potential in various ion separation system applications. At present, membrane separation has become one of the mainstream routes for lithium extraction from salt lakes. The core of membrane lithium extraction is membrane materials, but high-quality films are almost monopolized by foreign companies. This has led to my country's heavy reliance on imports for membrane materials used for lithium-magnesium separation in salt lake brines, which is costly and restricts large-scale applications.
[0004] Clay minerals are one of the most abundant minerals in the earth's crust. They are typical aluminosilicate minerals composed of silicon-oxygen tetrahedron and aluminum-oxygen octahedron structural units. They have natural nano-layered structures and excellent hydration expansion properties. They are easily peeled off into two-dimensional nanosheets under external force. The nanosheets have a two-dimensional structure with an extremely high aspect ratio, and the surface retains natural negative charge and double electric layer structure. They are ideal materials for preparing two-dimensional nanochannel membranes (ACS Nano 2022, 16, 4930-4939). Two-dimensional clay films have selective transmission behaviors for lithium-sodium, lithium-potassium, and lithium-magnesium ions, and show a selectivity of up to 380 times for the transmission of lithium-magnesium ions, which proves that two-dimensional clay films have the potential for selective ion transmission and have broad application prospects in the fields of lithium extraction from salt lakes, fuel cells, and seawater desalination. However, clay minerals have family diversity and a wide variety of types. Clay minerals from different origins have different amounts of isomorphic substitution in their lamellar structures due to differences in the mineralization environment, which in turn leads to different layer charge densities in the clay minerals, resulting in differences in the difficulty of exfoliating them to prepare two-dimensional nanosheets. Moreover, there are differences in clay minerals from different regions of the same origin, and the orderliness of the two-dimensional channel structures of different clay minerals after being cast into films is also different, that is, the difficulty of preparing two-dimensional nanochannel films from clay minerals is different.
[0005] Therefore, a method for screening clay minerals for preparing two-dimensional channel films is needed to quickly screen out clay mineral raw materials that meet the requirements for preparing two-dimensional channel films. Summary of the invention
[0006] The purpose of this application is to provide a method for screening clay minerals for preparing two-dimensional channel films, which can quickly and efficiently screen out clay minerals that are easy to peel and easy to build into films, filling the gap in the screening method of raw materials for two-dimensional clay channel films.
[0007] This application is implemented as follows:
[0008] The present application provides a method for screening clay minerals for preparing a two-dimensional channel film, comprising the following steps:
[0009] According to the layer charge density, clay minerals are divided into high layer charge density minerals, medium layer charge density minerals and low layer charge density minerals.
[0010] The high-charge density clay minerals, the middle-charge density minerals and the low-charge density minerals are dispersed into water at t 0 -t n The nanosheets were obtained by ultrasonic stripping in the time range, and the average sheet diameter a and average thickness b of various nanosheets were detected;
[0011] The average diameter a and average thickness b of various nanosheets are compared with the average diameter a of the target nanosheets. 0and average thickness b 0 For comparison: If b>b 0 , then the clay minerals corresponding to the nanosheets are not suitable for preparing two-dimensional channel films; if b≤b 0 , a 0 , then in the corresponding t 0 -t n Shorten the ultrasonic time within the time range to peel off the nanosheets and re-compare them. If b≤b 0 , a≥a 0 , then the nanosheet meets the size requirement; if b≤b 0 , a≥a 0 , the clay minerals corresponding to the nanosheets are not suitable for preparing two-dimensional channel films;
[0012] The clay mineral nanosheets meeting the size requirements are evenly dispersed in water to obtain a casting solution, and then filtered and dried to obtain a film to be tested;
[0013] Test the flatness c of the film to be tested and compare the flatness c of the film to be tested with the flatness c of the target film. 0 For comparison, if c <c 0 , clay minerals are not suitable for preparing two-dimensional channel films; if c ≥ c 0 , clay is suitable for preparing two-dimensional channel films.
[0014] In some optional embodiments, when clay minerals are divided into high charge density minerals, medium charge density minerals and low charge density minerals according to layer charge density, the charge density of high charge density clay minerals is 1, the charge density of medium charge density clay minerals is 0.6-0.9, and the charge density of low charge density clay minerals is 0.2-0.6.
[0015] In some optional embodiments, the layer charge density is tested by the following method: alkylamine is added to a water suspension of a clay mineral, which is then heated in a water bath and stirred, and then filtered and dried to obtain the clay mineral after alkylamine ion exchange; the clay mineral after alkylamine ion exchange is subjected to XRD testing to obtain the interlayer spacing; the distribution state of alkylammonium ions between clay mineral layers is determined based on the law of interlayer spacing changes, and the layer charge density of the clay mineral is then calculated.
[0016] In some optional embodiments, the carbon chain length of the alkylamine is 8-24, the amount of the alkylamine added is 1-5%wt of the clay mineral, the water bath heating temperature is 60-100°C, and the stirring time is 12-24h.
[0017] In some optional embodiments, the high charge density clay mineral has a 0 -t n When the nanosheets are obtained by ultrasonic exfoliation, 1-5 g of clay mineral is first dispersed in 100-500 mL of saturated LiCl solution, then stirred in a water bath at 60-100° C. for 12-24 h, the excess LiCl is washed off with deionized water, and then dispersed in 100-500 mL of deionized water, 2.5-5 g of octadecyltrimethylammonium chloride is added, and then stirred in a water bath at 80-100° C. for 12-36 h, the excess octadecyltrimethylammonium chloride is washed off with deionized water, and then dispersed in water to prepare a 0.5-1% wt clay mineral suspension for ultrasonic treatment, the ultrasonic power is 40-50 kHz, and the ultrasonic time range is t 0 22min, t n For 30 minutes.
[0018] In some optional embodiments, the intermediate charge density mineral is 0 -t n When the nanosheets are obtained by ultrasonic exfoliation, 1-4 g of clay mineral is first calcined at 750-950° C. in an air atmosphere for 4-10 h, and then the calcined clay mineral is dispersed in 100-800 mL of deionized water, 2-8 g of octadecyltrimethylammonium chloride is added, and then stirred in a water bath at 80-100° C. for 12-30 h, and the excess octadecyltrimethylammonium chloride is washed with deionized water and then dispersed in water to prepare a 0.5-1% wt clay mineral suspension for ultrasonic treatment, the ultrasonic power is 30-40 kHz, and the ultrasonic time range is t 0 12min, t n For 20 minutes.
[0019] In some optional embodiments, the low-layer charge density mineral is 0 -t n When the nanosheets are obtained by ultrasonic exfoliation, 1-3 g of clay mineral is first dispersed in 50-200 mL of saturated NaCl solution, then stirred in a water bath at 50-90° C. for 12-30 h, the excess NaCl is washed off with deionized water, and then dispersed in water to prepare a 0.5-1% wt clay mineral suspension for ultrasonic treatment, with an ultrasonic power of 10-20 kHz and an ultrasonic time range of t 0 is 2min, t n For 10 minutes.
[0020] In some optional embodiments, the average diameter a and average thickness b of the nanosheets are the arithmetic mean values of force microscopy statistical results of n nanosheet atoms, where n≥100.
[0021] In some optional embodiments, the average diameter of the target nanosheets is 0≥200nm, average thickness b 0 ≤5nm; and / or, the thickness of the film to be tested and the target film is 80-200μm.
[0022] In some optional embodiments, the flatness c is calculated using the following formula: c = 1 / sinθ, θ is the azimuth angle of the film obtained by the X-ray small angle scattering instrument test, and the flatness c of the target film is 0 ≥2.
[0023] The beneficial effects of the present application are as follows: the clay mineral screening method for preparing a two-dimensional channel film provided by the present application is to separate clay minerals into high-layer charge density minerals, middle-layer charge density minerals and low-layer charge density minerals according to the layer charge density and perform ultrasonic treatment and peeling to obtain nanosheets, and then screen the size and thickness of the nanosheets of the clay minerals to obtain nanosheets that meet the size of the two-dimensional clay film, and then prepare the nanosheets into a film for film flatness testing, and select clay materials that can prepare a highly ordered two-dimensional channel film. The clay mineral screening method for preparing a two-dimensional channel film provided by the present application can quickly and efficiently screen clay minerals that are easy to peel and easy to build into a film, filling the gap in the screening method of raw materials for two-dimensional clay channel films. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0025] Figure 1 A schematic flow chart of a method for screening clay minerals for preparing a two-dimensional channel film provided in an embodiment of the present application;
[0026] Figure 2 This is a small-angle X-ray scattering spectrum of a montmorillonite film screened by the clay mineral screening method for preparing a two-dimensional channel film provided in Example 1 of the present application. DETAILED DESCRIPTION
[0027] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application will be clearly and completely described below in combination with the drawings in the embodiments of the present application. Obviously, the described embodiments are only part of the embodiments of the present application, not all of the embodiments.
[0028] Therefore, the following detailed description of the embodiments of the present application provided in the accompanying drawings is not intended to limit the scope of the present application for which protection is sought, but merely represents selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.
[0029] The characteristics and performance of the clay mineral screening method for preparing a two-dimensional channel film of the present application are further described in detail below in conjunction with the examples.
[0030] like Figure 1 As shown, the embodiment of the present application provides a method for screening clay minerals for preparing a two-dimensional channel film, comprising the following steps:
[0031] S1. Clay minerals are divided into high-layer charge density minerals, middle-layer charge density minerals and low-layer charge density minerals according to layer charge density; optionally, the charge density of high-layer charge density clay minerals is 1, the charge density of middle-layer charge density clay minerals is 0.6-0.9, and the charge density of low-layer charge density clay minerals is 0.2-0.6;
[0032] Optionally, the layer charge density is obtained by the following alkylamine ion exchange method: a certain amount of alkylamine is added to the water suspension of clay mineral, and then filtered and dried after heating and stirring in a water bath to obtain the clay mineral after alkylamine ion exchange, and the clay mineral after alkylamine ion exchange is subjected to XRD test to obtain the interlayer spacing, and the distribution state of alkylammonium ions between the clay mineral layers is determined according to the law of interlayer spacing change, and then the layer charge density of the clay mineral is calculated. Optionally, the carbon chain length of the alkylamine is 8-24, the types of alkylamines with different carbon chain lengths added to the water suspension of the clay mineral are 6-10, the amount of alkylamine added is 1-5%wt of the clay mineral mass, the water bath heating temperature is 60-100°C, and the stirring time is 12-24h.
[0033] S2, disperse high-charge density clay minerals, middle-charge density minerals and low-charge density minerals into water at t 0 -t n time range for ultrasonic exfoliation to obtain nanosheets, and detect the average sheet diameter a and average thickness b of various nanosheets; optionally, the average sheet diameter a and average thickness b of the nanosheets are the arithmetic mean of force microscopy statistical results of n nanosheet atoms, n≥100.
[0034] Optionally, high charge density clay minerals at t 0 -t nWhen the nanosheets are obtained by ultrasonic exfoliation, 1-5 g of clay mineral is first dispersed in 100-500 mL of saturated LiCl solution, then stirred in a water bath at 60-100° C. for 12-24 h, the excess LiCl is washed off with deionized water, and then dispersed in 100-500 mL of deionized water, 2.5-5 g of octadecyltrimethylammonium chloride is added, and then stirred in a water bath at 80-100° C. for 12-36 h, the excess octadecyltrimethylammonium chloride is washed off with deionized water, and then dispersed in water to prepare a 0.5-1% wt clay mineral suspension for ultrasonic treatment, the ultrasonic power is 40-50 kHz, and the ultrasonic time range is t 0 22min, t n For 30 minutes.
[0035] The charge density of the intermediate layer minerals is 0 -t n When the nanosheets are obtained by ultrasonic exfoliation, 1-4 g of clay mineral is first calcined at 750-950° C. in an air atmosphere for 4-10 h, and then the calcined clay mineral is dispersed in 100-800 mL of deionized water, 2-8 g of octadecyltrimethylammonium chloride is added, and then stirred in a water bath at 80-100° C. for 12-30 h, and the excess octadecyltrimethylammonium chloride is washed with deionized water and then dispersed in water to prepare a 0.5-1% wt clay mineral suspension for ultrasonic treatment, the ultrasonic power is 30-40 kHz, and the ultrasonic time range is t 0 12min, t n For 20 minutes.
[0036] Low-charge density minerals at t 0 -t n When the nanosheets are obtained by ultrasonic exfoliation, 1-3 g of clay mineral is first dispersed in 50-200 mL of saturated NaCl solution, then stirred in a water bath at 50-90° C. for 12-30 h, the excess NaCl is washed off with deionized water, and then dispersed in water to prepare a 0.5-1% wt clay mineral suspension for ultrasonic treatment, with an ultrasonic power of 10-20 kHz and an ultrasonic time range of t 0 is 2min, t n For 10 minutes.
[0037] S3, the average sheet diameter a and average thickness b of various nanosheets are compared with the average sheet diameter a of the target nanosheet. 0 and average thickness b 0 For comparison: If b>b 0 , then the clay minerals corresponding to the nanosheets are not suitable for preparing two-dimensional channel films; if b≤b 0 , a 0 , then in the corresponding t0 -t n Shorten the ultrasonic time within the time range to peel off the nanosheets and re-compare them. If b≤b 0 , a≥a 0 , then the nanosheet meets the size requirement; if b≤b 0 , a≥a 0 , the clay minerals corresponding to the nanosheets are not suitable for preparing two-dimensional channel films; optionally, the average sheet size a of the target nanosheets 0 ≥200nm, average thickness b 0 ≤5nm;
[0038] S4, dispersing clay mineral nanosheets that meet the size requirements in water to obtain a casting solution, and then filtering and drying the film to be tested;
[0039] S5, testing the flatness c of the film to be tested, comparing the flatness c of the film to be tested with the flatness c of the target film 0 For comparison, if c <c 0 , clay minerals are not suitable for preparing two-dimensional channel films; if c ≥ c 0 , clay is suitable for preparing two-dimensional channel films. Optionally, the thickness of the film to be tested and the target film is 80-200 μm.
[0040] Optionally, the flatness c is calculated using the following formula: c = 1 / sinθ, where θ is the azimuth angle of the film obtained by a small-angle X-ray scattering instrument. Optionally, the flatness c of the target film is 0 ≥2.
[0041] The clay mineral screening method for preparing two-dimensional channel films provided in the embodiments of the present application summarizes the differences of clay minerals, classifies and summarizes the clay minerals according to layer charge density, size and thickness of exfoliated nanosheets, and channel orderliness of two-dimensional clay films, and screens different clay minerals by establishing a screening system, thereby quickly and efficiently selecting clay minerals suitable for preparing two-dimensional channel films.
[0042] Among them, by classifying clay minerals according to the size of their layer charge density and setting different stripping conditions for clay minerals with different charge densities, it is possible to ensure the stable stripping of nanosheets of different types of clay minerals, and screen out clay mineral nanosheets of suitable size and thickness that can be used to prepare thin films. Then, by targeted assembly of clay mineral nanosheets of qualified size and thickness into films and then conducting a film flatness test, clay minerals that can be used to prepare highly ordered two-dimensional channel films are screened out.
[0043] Example 1
[0044] The embodiment of the present application provides a method for screening clay minerals for preparing a two-dimensional channel film, wherein three montmorillonite clay minerals from different origins are screened and marked as montmorillonite No. 1, No. 2 and No. 3 respectively;
[0045] S1. Take 1g of three kinds of montmorillonite clay minerals respectively and add them to 6 100mL beakers. Add 2%wt of montmorillonite mass of hexaalkyltrimethylammonium chloride, octaalkyltrimethylammonium chloride, decanyltrimethylammonium chloride, dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride and hexadecyltrimethylammonium chloride to 6 100mL beakers of different kinds of montmorillonite respectively. Then add 60mL of deionized water respectively. Stir and disperse evenly and heat in a 100℃ water bath for 12h. Finally, centrifuge and dehydrate. After drying the precipitate, it is the alkylammonium intercalated montmorillonite sample. The layer charge density of No. 1, No. 2 and No. 3 montmorillonites is measured to be 0.47, 0.39 and 0.3 respectively.
[0046] S2. According to the layer charge density screening, montmorillonites No. 1, No. 2 and No. 3 are all clay minerals with low layer charge density;
[0047] 1 g of No. 1, No. 2 and No. 3 montmorillonite were dispersed in 100 mL of saturated NaCl solution, and then stirred in a 70°C water bath for 24 h. Excess NaCl was washed off with deionized water, and then a 0.5% wt clay mineral suspension was prepared. Nanosheets were obtained by exfoliation under ultrasonic power of 20 kHz for 10 min.
[0048] S3, using atomic force microscopy to measure the average diameter a of montmorillonite nanosheet No. 1 to be 450nm and the average thickness b to be 6nm, the average diameter a of montmorillonite nanosheet No. 2 to be 150nm and the average thickness b to be 2.5nm; the average diameter a of montmorillonite nanosheet No. 3 to be 500nm and the average thickness b to be 2nm;
[0049] By comparing the average diameter of the target nanosheets 0 is 200nm, the average thickness b 0 The results of comparative analysis showed that the No. 1 montmorillonite was not suitable and was directly eliminated. The No. 2 montmorillonite was further exfoliated with an ultrasonic power of 20kHz and an ultrasonic time of 8min. The average sheet diameter a of the prepared nanosheets was 250nm and the average thickness b was 3nm, which met the requirements and was cast. The No. 3 montmorillonite nanosheets met the requirements and were directly cast.
[0050] S4, taking 0.15g of the peeled No. 2 and No. 3 montmorillonite nanosheets respectively, adding deionized water and stirring to react to form a casting solution with a mass fraction of 0.5%, and using vacuum filtration to obtain a two-dimensional channel film with a membrane thickness of 100μm;
[0051] S5. The flatness of the No. 2 montmorillonite film was calculated by using a small-angle X-ray scattering instrument and was 1.2, which was less than the target flatness of 2 and did not meet the requirements, so it was eliminated. The flatness of the No. 3 montmorillonite film was 2.12 (see Figure 2 ), and selected No. 3 montmorillonite as the raw material of the two-dimensional channel film.
[0052] Figure 2 This is the X-ray small-angle scattering spectrum of the No. 3 montmorillonite film prepared in this example; it can be observed from the figure that the wide angle of the film is 28.1 degrees, and the flatness of the No. 3 montmorillonite film is calculated to be 2.12, indicating that the two-dimensional montmorillonite nanosheets are orderly stacked.
[0053] Example 2
[0054] The embodiment of the present application provides a method for screening clay minerals for preparing a two-dimensional channel film, wherein three clay minerals are screened, and the three clay minerals are mica, vermiculite and montmorillonite;
[0055] S1. Take 3g of three kinds of clay minerals and add them to 6 500mL beakers respectively. Add 5%wt of clay minerals to 6 500mL beakers of different kinds of clay minerals, octadecyltrimethylammonium chloride, decanyltrimethylammonium chloride, dodecyltrimethylammonium chloride, tetradecyltrimethylammonium chloride, hexadecyltrimethylammonium chloride and octadecyltrimethylammonium chloride respectively. Then add 400mL of deionized water respectively. Stir and disperse evenly and heat in a water bath at 80℃ for 24h. Finally, centrifuge and dehydrate. After drying the precipitate, it is the alkylammonium intercalated clay mineral sample. The layer charge density of mica, vermiculite and montmorillonite is measured to be 1, 0.7 and 0.33 respectively.
[0056] S2. According to the layer charge density screening, mica is classified as high layer charge density, vermiculite is classified as medium layer charge density, and montmorillonite is classified as low layer charge density;
[0057] 1 g of high-charge density clay mineral mica was dispersed in 100 mL of saturated LiCl solution, then stirred in a water bath at 100 ° C for 24 h, and the excess LiCl was washed off with deionized water. The washed clay mineral was then dispersed in 100 mL of deionized water, 2.5 g of octadecyltrimethylammonium chloride was added, and then stirred in a water bath at 100 ° C for 24 h, and the excess octadecyltrimethylammonium chloride was washed off with deionized water. Then, a 0.5% wt clay mineral suspension was prepared, and the nanosheets were exfoliated at an ultrasonic power of 50 kHz for 30 min.
[0058] 1 g of medium-density clay mineral vermiculite was calcined at 850° C. for 6 h in an air atmosphere, and then the calcined clay mineral was dispersed in 100 mL of deionized water, 2 g of octadecyltrimethylammonium chloride was added, and then stirred in a 100° C. water bath for 24 h, and the excess octadecyltrimethylammonium chloride was washed off with deionized water, and then a 0.5% wt clay mineral suspension was prepared, and the nanosheets were exfoliated by ultrasonication at a power of 40 kHz for 20 min;
[0059] 1 g of low-layer charge density clay mineral montmorillonite was dispersed in 100 mL of saturated NaCl solution, then stirred in a 70°C water bath for 24 h, excess NaCl was washed away with deionized water, and then prepared into a 0.5% wt clay mineral suspension, and exfoliated at 20 kHz ultrasonic power for 10 min to obtain nanosheets.
[0060] S3. The average diameter a of the mica nanosheets was 1000 nm and the average thickness b was 20 nm, the average diameter a of the vermiculite nanosheets was 800 nm and the average thickness b was 12 nm, and the average diameter a of the montmorillonite nanosheets was 620 nm and the average thickness b was 1.85 nm.
[0061] By comparing the average diameter of the target nanosheets 0 is 300nm, the average thickness b 0 A comparative analysis of 5nm found that mica and vermiculite were not suitable and were directly eliminated; montmorillonite nanosheets were directly cast into films;
[0062] S4. Take 0.25 g of the exfoliated montmorillonite nanosheets, add deionized water and stir to react to form a casting solution with a mass fraction of 2%, and use vacuum filtration to obtain a two-dimensional nanochannel film with a membrane thickness of 150 μm.
[0063] S5. The flatness of the montmorillonite film is calculated by using a small-angle X-ray scattering instrument and is found to be 3. Montmorillonite is selected as the raw material for the two-dimensional channel film.
[0064] The embodiments described above are part of the embodiments of the present application, rather than all of the embodiments. The detailed description of the embodiments of the present application is not intended to limit the scope of the present application for protection, but merely represents the selected embodiments of the present application. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.
Claims
1. A method for screening clay minerals for preparing two-dimensional channel films, characterized in that: Including the following steps: Classify clay minerals into high-layer charge density minerals, medium-layer charge density minerals, and low-layer charge density minerals according to the layer charge density; The high-charge density clay minerals, the middle-charge density minerals and the low-charge density minerals are dispersed into water at t0-t n time range for ultrasonic exfoliation to obtain nanosheets, and detecting the average sheet diameter a and average thickness b of the various nanosheets; Compare the average sheet diameter size a and the average thickness b of each of the nanosheets with the average sheet diameter size a0 and the average thickness b0 of the target nanosheet: If b > b0, the clay mineral corresponding to the nanosheet is not suitable for preparing a two-dimensional channel thin film; If b ≤ b0 and a < a0, then shorten the ultrasonic time within the corresponding t0 - t n time range for delamination to obtain nanosheets and re-compare. If b ≤ b0 and a ≥ a0 can be satisfied, the nanosheets meet the size requirements; If b ≤ b0 and a ≥ a0 cannot be satisfied, the clay mineral corresponding to the nanosheets is not suitable for preparing a two-dimensional channel thin film; Disperse the clay mineral nanosheets that meet the size requirements evenly in water to obtain a casting solution, and then filter and dry the film to obtain the film to be tested; Test the flatness c of the film to be tested, and compare the flatness c of the film to be tested with the flatness c0 of the target film. If c < c0, the clay mineral is not suitable for preparing a two-dimensional channel film; if c ≥ c0, the clay is suitable for preparing a two-dimensional channel film.
2. The method for screening clay minerals for preparing a two-dimensional channel film according to claim 1, characterized in that: When classifying clay minerals into high-layer charge density minerals, medium-layer charge density minerals, and low-layer charge density minerals according to the layer charge density, the charge density of the high-layer charge density clay mineral is 1, the charge density of the medium-layer charge density clay mineral is 0.6 - 0.9, and the charge density of the low-layer charge density clay mineral is 0.2 - 0.
6.
3. The method for screening clay minerals for preparing a two-dimensional channel film according to claim 1, characterized in that: The layer charge density is tested by the following method: Add alkylamine to the aqueous suspension of clay minerals, then heat and stir in a water bath, filter, and dry to obtain the clay minerals after alkylamine ion exchange. Perform XRD testing on the clay minerals after alkylamine ion exchange to obtain the layer spacing. Determine the distribution state of alkylammonium ions between the clay mineral layers according to the change law of the layer spacing, and then calculate the layer charge density of the clay minerals.
4. The method for screening clay minerals for preparing a two-dimensional channel film according to claim 3, characterized in that: The carbon chain length of the alkylamine is 8 - 24, the addition amount of the alkylamine is 1 - 5% wt of the mass of the clay minerals, the water bath heating temperature is 60 - 100°C, and the stirring time is 12 - 24 h.
5. The method for screening clay minerals for preparing a two-dimensional channel film according to claim 1, characterized in that: High charge density clay minerals at t0-t n When the nanosheets are obtained by ultrasonic exfoliation, 1-5 g of clay mineral is first dispersed in 100-500 mL of saturated LiCl solution, then stirred in a water bath at 60-100° C. for 12-24 h, the excess LiCl is washed off with deionized water and then dispersed in 100-500 mL of deionized water, 2.5-5 g of octadecyltrimethylammonium chloride is added, then stirred in a water bath at 80-100° C. for 12-36 h, the excess octadecyltrimethylammonium chloride is washed off with deionized water and then dispersed in water to prepare a 0.5-1% wt clay mineral suspension for ultrasonic treatment, the ultrasonic power is 40-50 kHz, t0 in the ultrasonic time range is 22 min, t n For 30 minutes.
6. The method for screening clay minerals for preparing a two-dimensional channel film according to claim 1, characterized in that: The charge density of the intermediate layer minerals is t0-t n When the nanosheets are obtained by ultrasonic exfoliation, 1-4 g of clay mineral is first calcined at 750-950° C. in an air atmosphere for 4-10 h, and then the calcined clay mineral is dispersed in 100-800 mL of deionized water, 2-8 g of octadecyltrimethylammonium chloride is added, and then stirred in a water bath at 80-100° C. for 12-30 h, excess octadecyltrimethylammonium chloride is washed with deionized water, and then dispersed in water to prepare a 0.5-1% wt clay mineral suspension for ultrasonic treatment, the ultrasonic power is 30-40 kHz, t0 in the ultrasonic time range is 12 min, t n For 20 minutes.
7. The method for screening clay minerals for preparing a two-dimensional channel film according to claim 1, characterized in that: Low-level charge density minerals at t0-t n When the nanosheets are obtained by ultrasonic exfoliation, 1-3 g of clay mineral is first dispersed in 50-200 mL of saturated NaCl solution, and then stirred in a water bath at 50-90° C. for 12-30 h, the excess NaCl is washed off with deionized water, and then dispersed in water to prepare a 0.5-1% wt clay mineral suspension for ultrasonic treatment, the ultrasonic power is 10-20 kHz, t0 in the ultrasonic time range is 2 min, t n For 10 minutes.
8. The method for screening clay minerals for preparing a two-dimensional channel film according to claim 1, characterized in that: The average sheet diameter size a and the average thickness b of the nanosheets are the arithmetic mean of the atomic force microscope statistical results of n nanosheets, where n ≥ 100.
9. The method for screening clay minerals for preparing a two-dimensional channel film according to claim 1, characterized in that: The average sheet diameter size a0 of the target nanosheets ≥ 200 nm, and the average thickness b0 ≤ 5 nm; and / or, the thickness of the film to be tested and the target film is 80 - 200 μm.
10. The method for screening clay minerals for preparing a two-dimensional channel film according to claim 1, characterized in that: The flatness c is calculated by the following formula: c = 1 / sinθ, where θ is the azimuth angle of the film tested by a small-angle X-ray scattering instrument, and the flatness c0 of the target film ≥ 2.
Citation Information
Patent Citations
Two-dimensional positively-charged sub-nano channel film for monovalent cation separation and preparation method and application of two-dimensional positively-charged sub-nano channel film
CN117983077A
Method of using nanosilica platelets to control water body eutrophication
TW201245050A
Two-dimensional tellurium nanosheet, manufacturing method therefor, and application thereof
WO2019153699A1
